Modelbuilder and Unit Hydrograph for Flood Prediction and Watershed Flow Direction Determination at The West Branch of The Little River, Stowe, Lamoille County, Vermont, USA - Florence Elfriede S. Silalahi; Fahrul Hidayat (Geoplanning: Journal of Geomatics and Planning, 2019)
The West Branch of the Little River in Stowe, Lamoille County, Vermont has been widely studied, and this area is regularly subject to flooding. The West Branch joins the Little River, which flows into the Winooski and drains into Lake Champlain. This area has undergone extensive development as an economic response to the ski resort industry over the past 50 years, and the recreational pathway is on the banks of the river. The Little River is adjusting to the loss of historic floodplain area, channel modifications (straightening and gravel mining), and runoff changes. In this project, a DEM with 10 and 30 meters resolution will be used to determine the watershed area for the outlet point at the south of Stowe for hydrological analysis. This project intends to describe the watershed flow direction with a unit hydrograph that shows when water discharge at the outlet is at its height during a rainfall event and produce the floods prediction map by predicting the nature of flood events to help in planning and responding to flood events effectively using ArcGIS Pro 2.0. The results show the time it takes water to flow to the outlet ranges from 0 seconds (rain that falls on the outlet itself) to over 8 hours and 46 minutes. The amount of water has accumulated, indicating that water will flow at its fastest when funneling toward the outlet point downstream of the town with no exception, indicating that water will flow at its fastest when funneling toward the outlet point downstream of the town.